2018
DOI: 10.1186/s13287-018-1098-4
|View full text |Cite
|
Sign up to set email alerts
|

A combination of ultrasound-targeted microbubble destruction with transplantation of bone marrow mesenchymal stem cells promotes recovery of acute liver injury

Abstract: BackgroundBone marrow mesenchymal stem cells (BMSCs) can provide an additional source of therapeutic stem cells for regeneration of liver cells during acute liver injury (ALI). However, the insufficient hepatic homing by the transplanted BMSCs limits their applications. Ultrasound-targeted microbubble destruction (UTMD) has been reported to promote the homing of transplanted stem cells into the ischemic myocardium. In this study, we investigated whether UTMD promotes the hepatic homing of BMSCs in ALI rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Despite the improvement in liver cancer in the last decades, the efficacy on this aggressive disease remains disappointing (Ding, 2016). Stem cells are a source of hepatocyte regeneration to repair the damaged liver, among which BMSCs have potential therapeutic value for liver diseases (Li, 2018). TDEs transfer the key factors from tumor cells to facilitate tumorigenesis, immune evasion and metastasis during HCC (Ba, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement in liver cancer in the last decades, the efficacy on this aggressive disease remains disappointing (Ding, 2016). Stem cells are a source of hepatocyte regeneration to repair the damaged liver, among which BMSCs have potential therapeutic value for liver diseases (Li, 2018). TDEs transfer the key factors from tumor cells to facilitate tumorigenesis, immune evasion and metastasis during HCC (Ba, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some articles have elucidated that SDF-1 and VCAM-1 expression is implicated in the liver homing of BMSCs ( 48 - 50 ). Recently, it has been revealed that increased VCAM-1 expression indicates that UTMD may induce BMSC migration by enhancing interstitial and intercellular capillary permeability ( 51 ). Furthermore, when the UTMD procedure is performed following a pre-injection of BMSCs, or when UTMD is combined with BMSC transplantation, there is a beneficial effect on the engraftment of cells ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the UTMD procedure is performed following a pre-injection of BMSCs, or when UTMD is combined with BMSC transplantation, there is a beneficial effect on the engraftment of cells ( 52 , 53 ). Ultrasound microbubbles can enhance the therapeutic effect of BMSCs in diseases and promote BMSC homing ( 51 , 54 , 55 ). In the present study, the BUTMD + siRNA NC group had an intermediate therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…This preliminary liver irradiation significantly promoted the homing and re-proliferation of BM-MSCs and significantly improved liver fibrosis in rat models [ 134 ]. Ultrasound-targeted microbubble destruction therapy effectively induces a favorable microenvironment for cell implantation, thus improving liver homing of BM-MSCs, which may be mediated by upregulation of adhesion molecules and cytokine expression [ 135 ]. Sun et al confirmed that combined application of BM-MSCs-HGF and ultrasound-targeted microbubble destruction technologies further promoted the homing of BM-MSCs and, more importantly, further improved their response to liver fibrosis [ 136 ].…”
Section: Strategies To Promote Msc Homing In the Treatment Of Liver D...mentioning
confidence: 99%